TATA KELOLA PERUSAHAAN DAN PENGUNGKAPAN LINGKUNGAN MELALUI LAPORAN TERINTEGRASI (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2021) - Ramadhani, Addien Safriya; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2024)
This study aims to fill a crucial gap by examining environmental disclosure in integrated reports in Indonesia. Specifically, this study will investigate corporate governance factors, board size, board independence, board gender diversity, and CSR committee, which are related to environmental disclosure levels in integrated reports in Indonesian companies. This study applies regression analysis using a sample of companies in Indonesia listed on the Indonesia Stock Exchange and publishing integrated reports for the 2021 period. By using purposive sampling in sample selection, 21 research samples were obtained for one year, in 2021. This research carries out an analysis to determine the effect between several corporate governance mechanisms and the level of environmental disclosure through integrated reports. The results of the research prove that board size, board gender diversity, and CSR committees have a positive and significant effect on environmental disclosure levels through integrated reporting. However, the research results also show that board independence has a negative and insignificant relationship with integrated reporting.